End of Life Intervention Program During COVID-19 in Vall d'Hebron University Hospital - Beneria, Anna; Castell-Panisello, Eudald; Sorribes-Puertas, Marta; Forner-Puntonet, Mireia; Serrat, Laia; García-González, Sara; Garriga, Maria; Simon, Carmen; Raya, Consuelo; Montes, Maria José; Rios, Giuliana; Bosch, Rosa; et al. (Frontiers in Psychiatry, 2021)
Introduction. The coronavirus disease 19 (COVID-19) and its consequences have placed our societies and healthcare systems under pressure. Also, a major impact on the individual and societal experience of death, dying, and bereavement has been observed. Factors such as social distancing, unexpected death or not being able to say goodbye, which might predict Prolonged Grief Disorder (PGD), are taking place. Moreover, hospitals have become a habitual place for End of Life (EOL) situations but not in the usual conditions because, for example, mitigation measures prevent families from being together with hospitalized relatives. Therefore, we implemented an EOL program with a multidisciplinary team involving health social workers (HSW) and clinical psychologists (CP) in coordination with the medical teams and nursing staff. Objectives. We aim to describe an EOL intervention program implemented during COVID-19 in the Vall d’Hebron University Hospital (HUVH). We present its structure, circuit, and functions. Descriptive analyses of the sample and the interventions that required psychological and social attention are reported. Material and methods. The total sample consists of 359 relatives of 219 EOL patients. Inclusion criteria were families cared for during the COVID-19 pandemic with family patients admitted to the HUVH in an EOL situation regardless of whether or not the patient was diagnosed with COVID-19. Results. Our program is based on family EOL care perceptions and the COVID-19 context features that hinder EOL situations. The program attended 219 families, of which 55.3% were COVID-19 patients and 44.7% had other pathologies. The EOL intervention program was activated in most of the EOL situations, specifically, in 85% of cases, and 78% of relatives were able to come and say goodbye to their loved ones. An emotional impact on the EOL team was reported. It is necessary to dignify the EOL situation in the COVID-19 pandemic, and appropriate psychosocial attention is needed to try to minimize future complications in grief processes and mitigate PGD.